2008
DOI: 10.1016/j.comppsych.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Are patients after severe injury who drop out of a longitudinal study at high risk of mental disorder?

Abstract: Are patients after severe injury who drop out of a longitudinal study at high risk of mental disorder? Are patients after severe injury who drop out of a longitudinal study at high risk of mental disorder? AbstractIn longitudinal studies of traumatic stress, it is particularly important to examine the data for any differences between those who drop out and those who continue to participate, because reluctance to participate might reflect symptoms of avoidance frequently seen in posttraumatic stress disorder (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…However, the rate and characteristics of non-completers in our study is comparable to other studies concerning long-term outcome of burn patients [45]. In a comparison of 15 different longitudinal studies concerning PTSD after severe injury, attrition rates of up to 55% were reported [46]. We dealt with the attrition rate in the present study by calculating ITT outcome analyses using linear mixed models, which are recommended for repeated measure data with many drop-outs [38,39].…”
Section: Discussionsupporting
confidence: 73%
“…However, the rate and characteristics of non-completers in our study is comparable to other studies concerning long-term outcome of burn patients [45]. In a comparison of 15 different longitudinal studies concerning PTSD after severe injury, attrition rates of up to 55% were reported [46]. We dealt with the attrition rate in the present study by calculating ITT outcome analyses using linear mixed models, which are recommended for repeated measure data with many drop-outs [38,39].…”
Section: Discussionsupporting
confidence: 73%
“…Second, the attrition rate was relatively high in this study, even though the patients who dropped out were not significantly different from those who participated in the follow‐up assessment in terms of the PDI and other covariates. In an earlier publication, we revealed that significant predictors of dropout were: male subjects, unconsciousness during MVA, low cooperativeness, and less severe injuries 38 . Participants with less severe injuries did not need to come to the NDMC for treatment after their discharge, which might affect the attrition rate.…”
Section: Discussionmentioning
confidence: 84%
“…Those who provided blood samples did not differ with respect to age, gender, or ISS from those who did not. We previously reported that dropouts prior to the 1-month assessment were likely to be male, unconscious during the MVA, have low cooperativeness, and have fewer severe injuries [16]. …”
Section: Methodsmentioning
confidence: 99%